The Influence of Service Quality and Product Quality on Indihome Customer Loyalty - Salehuddin, Salehuddin; Amri, Mohammah; Subagiono, Yoyok; Purwanto, Arik; Qomariah, Nurul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Technological developments are currently increasingly rapid along with the increasing need for technology in society. Very fast technological advances, especially in terms of ease of internet access, make the need for the internet increasingly increasing. This research aims to analyze and determine the role of service quality and product quality on customer loyalty at PT Telkom Jember. The population in this research is all PT Telkom Jember customers who use Indihome products. The planned sample size was determined as 75 respondents. The analytical tools used are description analysis, validity test analysis, reliability and classical assumptions as well as research hypothesis test analysis. The results of this research are expected to show that service quality and product quality can provide a significant increase in customer loyalty at PT Telkom Jember. With good service quality, it is hoped that customers will have increased loyalty. With good product quality, it is also hoped that customer loyalty will also increase.